Employee Engagement Affected By Transformational Leadership And Intrinsic Motivation : Case Study Pt. Telkomsel Branch Medan Area - Suhartini (Publisher Cv. Inara, 2022)
The purpose of this study was to determine the effect of transformational leadership on employee engagement, to determine the effect of intrinsic motivation on employee engagement, to determine the effect of transformational leadership and intrinsic motivation on employee engagement. This research uses a quantitative approach. As for the population in this study are employees of PT. Telkomsel Medan Area Branch totals 65 people. Saturated sampling technique is a sampling technique when all members of the population are used as samples so that the sample used in this study is 65 people. The results of this study on hypothesis 1 obtained the results of tcount > ttable (2.534 > 1.998) with a significance level of 0.01 (0.01 < 0.05), it can be concluded that there is a significant effect of Transformational Leadership on employee engagement. Hypothesis 2 obtained the results of tcount > ttable (3.337 > 1.998) with a significance level of 0.00 (0.00 < 0.05), it can be concluded that there is a significant effect of intrinsic motivation on employee engagement. Hypothesis 3 there is an influence between Transformational Leadership and intrinsic motivation on employee engagement at PT. Telkomsel Medan Area Branch obtained Fcount > Ftable (10.120 > 3.145) with a significance level of 0.00 (0.00 < 0.05) thus H0 is rejected and H1 is accepted which means there is a significant influence between Transformational Leadership and intrinsic motivation to employee engagement. The conclusion of this study is that there is a significant influence between Transformational Leadership on employee engagement at PT. Telkomsel Medan Area Branch, there is a significant influence between intrinsic motivation on employee engagement at PT. Telkomsel Medan Area Branch and there is an influence between Transformational Leadership and intrinsic motivation on employee engagement at PT. Telkomsel Medan Area Branch